Maqashid Al-Shariah Analysis of Child-Rearing Wills (Wasiat Tarbiyah) Under Article 156 (A) of the Compilation of Islamic Law - Nadila Putri; Sabilul Muhtadin (Fakultas Agama Islam, 2026)
This study aims to analyze the practice of child-rearing wills (wasiat tarbiyah) from the perspective of maqashid al-shariah and its conformity with Article 156(a) of the Compilation of Islamic Law. Children are subjects of legal protection whose continuity of care must be planned by parents, including through testamentary arrangements. However, the practice of wasiat tarbiyah often creates tension with the custodial order (hadhanah) regulated in the Compilation of Islamic Law. This study employs a normative legal method with statutory and conceptual approaches. Primary legal sources include the Qur’an, Hadith, the Compilation of Islamic Law, and classical Islamic jurisprudence texts, while secondary sources consist of scholarly journals and relevant academic books. Data collection is conducted through library research using descriptive-analytical analysis based on maqashid al-shariah. The findings indicate that wasiat tarbiyah has a strong legal foundation in Islamic jurisprudence, although differences exist compared to the formal custodial order in the Compilation of Islamic Law. The principle of the child’s best interest (maslahah) becomes the main consideration, allowing deviations from the prescribed order when it better serves the child’s welfare. From the perspective of maqashid al-shariah, this practice aligns with hifz al-nafs, hifz al-aql, and hifz al-nasl. The study concludes that wasiat tarbiyah is a child protection instrument that should be formally documented in writing to prevent conflicts and ensure the realization of the child’s welfare.